ANALISIS PSIKOLOGI SASTRA TOKOH UTAMA DALAM NOVEL LUPUS “TANGKAPLAH DAKU KAU KUJITAK” KARYA HILMAN HARIWIJAYA, DAN NOVEL DILAN “DIA ADALAH DILANKU TAHUN 1990” KARYA PIDI BAIQ - Muhammad Faridh Wazdy (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
This paper is written to provide an overview to the reader, that in the Lupus novel "Tangkaplah Daku Kau Kujitak" by Hilman Hariwijaya and Dilan 1990 novel "Dia dilanku" by Pidi Baiq which appeared in 1980-2000 there are similarities. This study uses a qualitative method to analyze the novel Lupus and Dilan. This study aims to determine the personal psychology of the main character contained in the two novels through the classification of emotions, such as the concept of guilt, buried guilt, self-punishment, shame, sadness, hatred and love. Keyword: Hilman Hariwijaya, Pidi Baiq, Lupus, Dilan, Psychology.